The future of tourism: interview with Bernadett Papp on bringing equity into debates on tourism development and destination governance - Stefan Hartman; Bernadett Papp (Journal of Tourism Futures, 2024)
Purpose – As the Journal of Tourism Futures celebrates its 10th Anniversary, Dr Stefan Hartman (head of department at the European Tourism Futures Institute, NHL Stenden University of Applied Sciences) interviews Bernadett Papp (senior researcher at the European Tourism Futures Institute (ETFI) at NHL Stenden University of Applied Sciences) about her recent work in tourism practice and academic and future perspectives on topics relevant to the future of tourism. Design/methodology/approach – A personal interview was held on September 16, 2024. Findings – Bernadett Papp draws attention to the importance of bringing equity into debates on tourism development and destination governance. She sees a crucial role for governments, the redesign of institutional frameworks, monitoring and data collection and rethinking systems of governance. Originality/value – The interview provides unique insights into the viewpoints of Papp, highlighting the importance of the still understudied topic of equitable tourism. A topic that still requires a lot of work before hitting mainstream approaches to destination development, even though it should have been on the policy agendas for many years already.